2014
DOI: 10.18632/oncotarget.3202
|View full text |Cite
|
Sign up to set email alerts
|

Age and metabolic risk factors associated with oxidatively damaged DNA in human peripheral blood mononuclear cells

Abstract: Aging is associated with oxidative stress-generated damage to DNA and this could be related to metabolic disturbances. This study investigated the association between levels of oxidatively damaged DNA in peripheral blood mononuclear cells (PBMCs) and metabolic risk factors in 1,019 subjects, aged 18-93 years. DNA damage was analyzed as strand breaks by the comet assay and levels of formamidopyrimidine (FPG-) and human 8-oxoguanine DNA glycosylase 1 (hOGG1)-sensitive sites There was an association between age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 55 publications
2
23
0
3
Order By: Relevance
“…Moreover, body weight loss resulted in a reduction in the level of DNA damage [104][105][106][107]. The amount of DNA with oxidative damage was associated with levels of cholesterol, triglycerides and HbA1c [108]. In the present study a relationship between DNA damage and both, total cholesterol and LDLcholesterol was also observed.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, body weight loss resulted in a reduction in the level of DNA damage [104][105][106][107]. The amount of DNA with oxidative damage was associated with levels of cholesterol, triglycerides and HbA1c [108]. In the present study a relationship between DNA damage and both, total cholesterol and LDLcholesterol was also observed.…”
Section: Discussionsupporting
confidence: 70%
“…Lohr et al also confirmed this finding. Authors of that study indicated that the blood pressure was not associated with the oxidatively damaged DNA levels among individuals with MetS (23). By contrast, Najarzadeh et al (24) and Bitla et al (19) showed a significant correlation among these variables.…”
Section: Discussionmentioning
confidence: 90%
“…Age increase especially in women can elevate the risk of OxS (1,5,23). Previous data also revealed higher protein oxidation level in women compared to men.…”
Section: Mda Tac ----------------------------------------------------mentioning
confidence: 98%
“…We usually find substantially higher levels of FPG-sensitive sites than of hOGG1-sensitive sites in human PBMC samples, although the levels of FPG-and hOGG1-sensitive sites are similar and high after treatment with the photosensitizer Ro19-8022 or potassium bromate inducing specifically 8-oxodG [16][17][18].…”
Section: Collection and Analysis Of Biomarker Samplesmentioning
confidence: 84%